An item-analysis and validity study of the science education center elementary mathematics tests for grades 1, 2, and 3 - Vitug, Carolina P. 1944-
The study attempts to determine the validity and reliability of the Science Education Center Elementary School Mathematics Achievement Tests for grades I to III. It also aims to analyze the test items and point out areas for improvement. The study concludes that there is still a need for improving the reliability coefficient of correlation of the tests.